Prevalence and Clinical Characteristics of Low Back Pain among Operating Room Personnel: A Cross-Sectional Study in South of Iran - Fayzi, Reza; Karimi, Ashkan; Fereidouni, Armin; Salavatian, Armin; Imani, Behzad; Tavakkol, Reza (Frontiers in Surgery, 2022)
Background: Low back pain is one of the most common musculoskeletal disorders and the most common cause of activity restriction in people younger than 45 years. Nurses have a high incidence of Low back pain due to physical and emotional factors among health care workers. The purpose of this study was to evaluate the prevalence and clinical characteristics of low back pain. Methods: This cross-sectional study that was performed on 385 operating room personnel of the hospitals affiliated to Shiraz (The largest city in southern Iran) University of Medical Sciences. The data were collected through a researcher-made questionnaire. The questionnaire consisted of two parts, including the demographic information and prevalence and dimensions of low back pain. Results: The results showed that the prevalence of low back pain was 74% among operating room personnel. There was a significant relationship between low back pain and education level and marital status (P<0.05). Conclusion: Hospital managers should reduce the prevalence of this disorder among operating room staff by teaching preventive techniques through training courses.